Study on the Involute Spline Measurement Method - Lu Qiulong; Wang Yunxiang (Jixie chuandong)
The research history and current situation of involute spline is briefly summarized. The new development and application status of involute spline technology in recent years is more systematically introduced. It mainly focuses on study of design and development stage of involute spline，selection of reference standard of involute spline，calculation optimization and measurement of involute spline，as well as the research of fixture used for measurement，and share our measurement method. It is proposed to update the measuring equipment and improve the measuring accuracy，collaboration is needed to integrate software standards，carry out accurate calculation，remove conversion approximation and so on.